PEMBELAJARAN LITERASI DAN NUMERASI DI SMP ISLAM NURUL YAQIN DALAM PEMBELAJARAN SENI BUDAYA - Hayati, Maylisa; supriyadi, edi (Papanda Publisher, 2022)
The purpose of this study is to provide information about learning Cultural Arts to all students of Nurul Yaqin Islamic Junior High School in the even semester of the 2021/2022 academic year. This research is to discuss about learning art and culture by applying literacy and numeracy systems. Bearing in mind that the issues discussed in this article are about the application of Literacy and Numeration learning to Cultural Arts learning in class VIII A-C, namely visual arts and music/vocal arts. This research was conducted at Nurul Yaqin Islamic Junior High School, which is located on Jl. Ciakar Ds. Leuwidulang District. Sodonghilir Kab. Tasikmalaya. The results of the study show that by giving this cultural arts learning, it can seek students' knowledge of art insights from those who are only considered to know to know how art is and how to learn it even the responses of the students themselves are very exsaited, so it can be concluded both theoretically and empirically through this service can seek new knowledge for all students, especially in Islamic Junior High School Nurul Yaqin itself regarding learning this Cultural Arts.